2016
DOI: 10.1080/13573322.2016.1184135
|View full text |Cite
|
Sign up to set email alerts
|

Re-engaging ‘youth at risk’ of disengaging from schooling through rugby league club partnership: unpacking the pedagogic practices of the Titans Learning Centre

Abstract: The youth learning re-engagement program known as the Titans Learning Centre (or TLC) is an approved alternative schooling program, developed in partnership with state education and a local National Rugby League (NRL) club, the 'Titans'. Students typically in Grade Three or Four complete a 10 week program, interacting with professional A grade NRL players on a weekly basis during classroom learning time and lunch time 'handball' sessions. The project sought to understand the pedagogic practices of the TLC, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…The phenomenon of high profile athletes/players as community role models within in-curricular programs has received extensive attention in the literature (cf. Armor and Duncombe, 2012) and our research illustrated that a consistent message was shared by these players to the students in their weekly visitspersist, acknowledge set-backs, show empathy and respect those around you (Whatman and Main, 2016). Analysis of anecdotal data collected by the TLC teachers, and by the research team (also including player interviews and parent correspondence), indicated that even the briefest of meetings with a high profile community member who had taken the time to show an interest in the TLC participants' learning journey made a positive and lasting impression on them.…”
Section: Youth Wellbeing Insupporting
confidence: 56%
“…The phenomenon of high profile athletes/players as community role models within in-curricular programs has received extensive attention in the literature (cf. Armor and Duncombe, 2012) and our research illustrated that a consistent message was shared by these players to the students in their weekly visitspersist, acknowledge set-backs, show empathy and respect those around you (Whatman and Main, 2016). Analysis of anecdotal data collected by the TLC teachers, and by the research team (also including player interviews and parent correspondence), indicated that even the briefest of meetings with a high profile community member who had taken the time to show an interest in the TLC participants' learning journey made a positive and lasting impression on them.…”
Section: Youth Wellbeing Insupporting
confidence: 56%
“…This is surprising as research shows that effective social and emotional learning (SEL) programs can have immediate and long-lasting positive effects on students, and the timing of the programs' delivery is also important [4]. Within the classroom, SEL programs are typically characterized by approaches that support self-management, responsible decision-making, relationship skills, social awareness, and self-awareness [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Jeffs and Smith (2005) feel that a key task of youth workers is to create favorable learning environments including social and experiential facets. Although there are numbers of studies on different aspects of youth sports clubs such as Light et al (2013) on why children join and stay in clubs, Whatman and Main (2018) on re-engaging youth at risk and Shaikh and Forneris (2018) on influence of coaches, there is limited research focussing on the experiences of the key stakeholders in this learning environment. Stewart and Jordan (2017) advocate that studies are needed regarding learning opportunities in informal contexts.…”
Section: Introductionmentioning
confidence: 99%